(3GdMce GdShGHZ Ydi Gdcde GdfhGHZs - (3UdGM GdOjf eMeO Hf Ydj Hf eMeO Hf Ydj GdRjOj, GdfGUQ dOjf Gddg,J (B793 (3g` s
(3ChdgG (B:s
(3jbhd GdeZehQ HCehQ GdZadI hdeG cGf GdYde MjGI GdCOjGf hfLGI GdCHOGf, SGYOJ HYV ENhGfj aj JjSjQ CdaGX fhGHZ Gdcde ddTjN GdEeGe GdYdGeI LGQGddg GdReNTQj, aUeOJ EdjgG eY GYJQGaj HbUhQ GdHGY s
(3BNQgG (B:s
(3bGd GdTGYQ(B: (3GdOgQ CHdGfj heG CHdjJg hGdOgQ ZjQfj heG jJZjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B261 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs